Effect of Ligands on HP-Induced Unfolding and Oligomerization of β-Lactoglobulin - Minić, Simeon (Biophys J, 2020)
To probe intermediate states during unfolding and oligomerization of proteins remains a major challenge. High pressure (HP) is a powerful tool for studying these problems, revealing subtle structural changes in proteins not accessible by other means of denaturation. Bovine β-lactoglobulin (BLG), the main whey protein, has a strong propensity to bind various bioactive molecules such as retinol and resveratrol, two ligands with different affinity and binding sites. By combining in situ HP-small-angle neutron scattering (SANS) and HP-ultraviolet/visible absorption spectroscopy, we report the specific effects of these ligands on three-dimensional conformational and local changes in BLG induced by HP. Depending on BLG concentration, two different unfolding mechanisms are observed in situ under pressures up to ∼300 MPa: either a complete protein unfolding, from native dimers to Gaussian chains, or a partial unfolding with oligomerization in tetramers mediated by disulfide bridges. Retinol, which has a high affinity for the BLG hydrophobic cavity, significantly stabilizes BLG both in three-dimensional and local environments by shifting the onset of protein unfolding by ∼100 MPa. Increasing temperature from 30 to 37°C enhances the hydrophobic stabilization effects of retinol. In contrast, resveratrol, which has a low binding affinity for site(s) on the surface of the BLG, does not induce any significant effect on the structural changes of BLG due to pressure. HP treatment back and forth up to ∼300 MPa causes irreversible covalent oligomerization of BLG. Ab initio modeling of SANS shows that the oligomers formed from the BLG-retinol complex are smaller and more elongated compared to BLG without ligand or in the presence of resveratrol. By combining HP-SANS and HP-ultraviolet/visible absorption spectroscopy, our strategy highlights the crucial role of BLG hydrophobic cavity and opens up new possibilities for the structural determination of HP-induced protein folding intermediates and irreversible oligomerization.